2022
DOI: 10.1002/ehf2.14020
|View full text |Cite
|
Sign up to set email alerts
|

Oral iron supplementation in patients with heart failure: a systematic review and meta‐analysis

Abstract: Aims This review aimed to assess whether oral iron supplementation in a chronic heart failure (HF) population with iron deficiency (ID) or mild anaemia is safe and effective according to evidence‐based medicine. Methods We retrieved 1803 records from the PubMed, Embase, and the Cochrane Library databases from 1 January 1991 to 15 September 2021. The clinical outcome of oral iron supplementation for ID anaemia in patients with HF was the primary endpoint. The primary safety measures included adverse events and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Indeed, the beneficial effects of treating iron deficiency in HF have been highlighted by several meta‐analyses that demonstrated that intravenous iron infusion in patients with HF reduces the composite risk of first hospitalization for HF and cardiovascular mortality as well as the risk of first and recurrent hospitalizations for HF, with no or negligible effect on all‐cause mortality or cardiovascular mortality alone 40,41 . Another recent meta‐analysis has shown that oral iron supplementation can increase serum iron levels in patients with HF and ID or mild anaemia but does not improve transferrin saturation and the distance covered in the 6‐minute walking test 42 . In addition, oral iron supplementation is relatively safe.…”
Section: Treatmentmentioning
confidence: 99%
“…Indeed, the beneficial effects of treating iron deficiency in HF have been highlighted by several meta‐analyses that demonstrated that intravenous iron infusion in patients with HF reduces the composite risk of first hospitalization for HF and cardiovascular mortality as well as the risk of first and recurrent hospitalizations for HF, with no or negligible effect on all‐cause mortality or cardiovascular mortality alone 40,41 . Another recent meta‐analysis has shown that oral iron supplementation can increase serum iron levels in patients with HF and ID or mild anaemia but does not improve transferrin saturation and the distance covered in the 6‐minute walking test 42 . In addition, oral iron supplementation is relatively safe.…”
Section: Treatmentmentioning
confidence: 99%
“…A statistical study has shown that iron supplementation can reduce the hospitalization rate of patients with HF, enhance heart function, and improve quality of life [ 129 ]. Oral iron supplements commonly used include ferrous salts (such as ferrous sulfate) and dextran iron, lactoferrin, and ferritin complex, etc.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“… 1 , 98–106 Elevated levels of hepcidin explain why—following oral iron supplementation—patients with heart failure do not show an improvement in exercise capacity, 107–109 and only a minority (those without systemic inflammation and preserved gastrointestinal absorption 110 ) show changes in TSAT or serum ferritin. 107 , 109 , 111 Furthermore, higher serum ferritin levels (which are closely related to skeletal muscle ferritin but inversely related to skeletal muscle TfR1 91 , 112 ) cause intracellular sequestration and further depletion of cytosolic Fe 2+ . Therefore, in patients with heart failure, modest hypoferraemia—insufficient to cause anaemia—may trigger a disproportionate depletion of intracellular iron within skeletal myocytes, 113 especially when inflammation or immobilization (acting in concert) have already drained the cytosolic iron pool.…”
Section: Type 2 Iron-deficient Heart Failure: Heart Failure-related I...mentioning
confidence: 99%